Self-care and Quality of Life in Patients with Chronic Renal Failure Undergoing Hemodialysis at Sulaimaniyah Province, Kurdistan Region of Iraq - Ibrahim, Khalil Hamad; Ismael, Niyan Hakim (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Chronic renal failure (CRF) is a significant and growing public health issue globally with a negative impact on self-care and quality of life (QoL). Self-care and QoL are essential aspects of controlling the adverse effects of the illness. Objectives: To assess self-care and QoL of patients with CRF who undergo hemodialysis (HD). Patients and methods: A descriptive-analytical design was carried out in Sulaimani Province Hemodialysis Centers/Unit from March to September 2022. About 150 patients with CRF undergoing hemodialysis consented to participate in the study. Non-probability convince sample technique was used to select the participants. The data were collected through a questionnaire by direct interview. Results: Most patients were ≥60 years, males, married, illiterate, lived in an urban area and had barely sufficient economic status with 4-6 family members. The study's findings revealed inadequate self-care in >50% of patients. A significant correlation between selfcare and QoL in limitation of activities was found for CRF patients who underwent Hemodialysis with no correlation for general health, physical and emotional, and energy and emotion. Also, there was a significant difference between QoL and age (for the general health domain), gender, and level of education (for the limitations of the activities domain). Mean self-care measurement was significantly associated between previous occupation and duration of Hemodialysis. Conclusions: Most patients had inadequate self-care and poor QoL, which means that higher self-care performance was associated with better QoL in the limitation of activities only and no other QoL domains.
Keywords: Chronic renal failure; hemodialysis; selfcare; quality of life; descriptive analytical study